FACTORS AFFECTING TURNOVER INTENTION AMONG GENERATION Z EMPLOYEES WORKING IN THE FINTECH SECTOR IN JAKARTA - Nita Susanti; Yanuar Yanuar (Graduate Program of Universitas Tarumanagara, 2025)
This study aims to analyze the effect of work overload, work-life balance, toxic leadership, and work stress on turnover intention among Generation Z employees working in the financial technology sector, with job burnout is considering as a mediating variable. Generation Z is known for its dynamic work characteristics, strong emphasis on life balance, and heightened sensitivity to high-pressure work environments, making turnover between this cohort an important issue. This research is taking a quantitative approach by using a survey method, and the data were analyzed with Structural Equation Modeling (SEM). The sampling method used was non-probability sampling, specifically purposive sampling. A total of 231 Generation Z employees successfully participated as respondents. The results shows that work overload, work-life balance, and toxic leadership have a positive and significant effect on turnover intention among Generation Z employees. Job burnout is also considered to have a positive and significant effect on turnover intention. However, work stress does not have a direct effect on turnover intention. In addition, work stress greatly affects job burnout, and job burnout substantially mediates the relationship between work stress and turnover intention. This study is taking contribution by emphasizing the essential role of burnout as the psychological pathway through which workplace stressors lead to turnover intention. The findings offer practical implications for organizations to amplify workload management, improve leadership practices, and improve employee well-being initiatives to lessen burnout and support retention.